2005
DOI: 10.1086/462427
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis and Susceptibility to HIV Infection in South African Women: A Nested Case‐Control Study

Abstract: BV may account for a substantial fraction of new HIV infections in this setting. Treatment of BV and other interventions to promote normal vaginal flora warrant attention for HIV prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
168
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(176 citation statements)
references
References 40 publications
7
168
0
1
Order By: Relevance
“…Bacterial [15]. It has been documented that bacterial vaginosis propagates viral replication and vaginal shedding of the HIV-1 and HSV-2 viruses, thereby further enhancing the spread of these sexually transmitted diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial [15]. It has been documented that bacterial vaginosis propagates viral replication and vaginal shedding of the HIV-1 and HSV-2 viruses, thereby further enhancing the spread of these sexually transmitted diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 . Several studies have demonstrated the possibility of an association between bacterial vaginosis and transmission of HIV 3 . One of the methods of diagnosis of bacterial vaginosis is by Nugent's criteria based on evaluation of normal flora in gram stained smears of vaginal discharge 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the use of long term, low dose suppressive therapy for BV. Other studies also suggest that the incidence of BV increases the risk of sexually transmitted infections [10], and therefore, it is essential to develop new approaches to the preservation of a healthy vagina, particularly therapies which can be readily available, economical and with a higher efficacy in terms of reducing recurrences.…”
Section: Introductionmentioning
confidence: 99%